The order of things an archaeology of the human sciences - Foucault, Michel 1926-1984 (Routledge classics., 2002)
When one defines 'order' as a sorting of priorities, it becomes beautifully clear what Foucault is doing here. He weaves an intensely complex history of thought. He dips into literature, art, economics and even biology.